Surrounded by sharks - Northrop, Michael (Scholastic Press, 2014)
On the first day of vacation thirteen-year-old Davey Tsering wakes up early, slips out of his family's hotel room without telling anyone, and heads for the beach and a swim in the warm Floridian waters--and a fateful meeting with a shark.